Pengaruh Penambahan Beberapa Konsentrasi Pupuk NPK dan Air Asam Tambang Pada Proses Fitoremediasi oleh Eleocharis dulcis (Burm. F) Trin. Ex. Henschel - Febi Arisandy; Sri Pertiwi Estuningsih; Juswardi Juswardi (Faculty of Mathtmatics and Natural Sciences, 2018)
This research aims to see the effect of adding some concentration of NPK fertilizer and acid mine drainage can improve phytoremediation process using Eleocharis dulcis. This research was conducted in Plant Physiology Laboratory of Biology Department of FMIPA Sriwijaya University, and Laboratory of Balai Teknik Kesehatan Lingkungan dan Pengendalian Penyakit Kelas I Palembang, South Sumatera. The design used in this research was a Randomized Block Design of a factorial pattern consisting of two factors: NPK fertilizer concen-tration (0 mg / L, 500 mg / L, 750 mg / L, and 1000 mg / L) and AMD waste (0% 25%, and 50%), each treatment combination was repeated 3 times. Data were analyzed by analysis of variance (ANOVA), mean difference be-tween treatments was done using Duncan Multiple Range Test (DMRT) test at α 5% level. The results showed Eleocharis dulcis at AMD concentration of 50% with addition of fertilizer 750 mg / L able to improve process of phytoremediation of AMD. E. dulcis was able to reduce good Mn concentration at AMD concentration 50% with addition of NPK fertilizer 750 mg / L that is 2.77 mg / L. Change of pH at concentration AMD 50% with addition of NPK fertilizer 750 mg / L that is 6,0. Dry weight of Eleocharis dulcis after phytoremediation at AMD concentration 50% with addition of NPK fertilizer 750 mg / L ie 13.58 g.